INFLUENCE OF ZINC, CALCIUM AND BORON ON VEGETATIVE AND FLOWERING PARAMETERS OF GLADIOLUS CV. ALDEBRAN - SHARMA, JYOTI; A. K. GUPTA,; KUMAR, CHANDAN; R. K. S GAUTAM, (The Bioscan, 2012)
An experiment was carried out at, Chandra Shekhar Azad University of Agriculture and Technology, Kanpur during the year 2010-11. The experiment consisted two levels each of Zn (Zn0 and Zn1), Ca (Ca0 and Ca1) and B (B0 and B1) which were sprayed on gladiolus plant. The dose of foliar spray of Zn, Ca and B were 0.75%, 0.50% and 0.20%, respectively. The height of plant significantly increased by foliar application of Zn, B, and Ca (79.55 cm, 79.39 cm and 78.75, respectively) interaction effect was also significant between those. The yield of spike increased significantly with foliar application of zinc and calcium, maximum yield of spike (16904.50) was recorded with application of zinc 0.75%. The length of floret was significantly enhanced by the use of B (8.29) and Zn (8.23) while, effect of Ca was non-significant. Spray of calcium was found most effective in prolonging the longevity of spike (17.61 days) as compare to control (14.79 days) and more corms (3.30) were produced in the plants fertilized with zinc. Results obtained among, from the application of Zn, B and Ca and its interaction Zn exhibited most significant effect on various parameters studied under the investigation.